Family Support Interventions in Hemodialysis Patients :A Systematic Review - Nur Kasan; Yunie Armiyati; Chanif Chanif (Universitas Pahlawan Tuanku Tambusai, 2026)
Introduction: Patients undergoing hemodialysis in hospitals are often faced with a variety of complex physical, psychological and social challenges. Family support has been identified as a key factor in improving patients' quality of life and adherence to therapy. Family support interventions for hemodialysis patients can help address issues related to the decline in quality of life. Objective: This study aims to examine the relationship between family support interventions and self-care behaviors and the quality of life of chronic kidney patients undergoing hemodialysis. Methods: This study was conducted using nine articles obtained between April 2 and May 18, 2025. Results: A total of nine relevant research articles were identified and analyzed, revealing a positive relationship between family support interventions and both self-care behavior and the quality of life of chronic kidney patients undergoing hemodialysis. Several factors were found to influence the effectiveness of these interventions, including patient characteristics, family conditions, the type and intensity of the intervention, socioeconomic factors, and the role of healthcare professionals. However, some aspects remain underexplored, such as family emotional intelligence, multigenerational family dynamics, the role of technology in family support, family spirituality, caregiver burnout, and family perceptions and expectations regarding treatment outcomes. Conclusion: Family support interventions can enhance self-care behavior and improve the quality of life of hemodialysis patients.